MANAGEMENT OF LOCAL WISDOM CENTER FOR THAI MASSAGE - Phusit, Rattigan (Academic Journal of Thailand National Sports University, 2019)
This mixed method study aimed to develop an effective business strategy model for local wisdom center for thai message. Participants of this study were 28 masseurs from the Wat Ban Na Local Wisdom Center for Thai Massage, Results revealed that the business strategy model of local wisdom center for thai massage consist of corporate strategies employed growth strategy and focused on expertise and external resources alliance strategy; business strategy which employed making different strategy; operational strategy uses cost-control and maximizing profit strategy.